2012
DOI: 10.1371/journal.pone.0034995
|View full text |Cite
|
Sign up to set email alerts
|

Two Homologous Putative Protein Tyrosine Phosphatases, OsPFA-DSP2 and AtPFA-DSP4, Negatively Regulate the Pathogen Response in Transgenic Plants

Abstract: Protein phosphatases, together with protein kinases, regulate protein phosphorylation and dephosphorylation, and play critical roles in plant growth and biotic stress responses. However, little is known about the biological functions of plant protein tyrosine dual-specificity phosphatase (PFA-DSP) in biotic stresses. Here, we found that OsPFA-DSP2 was mainly expressed in calli, seedlings, roots, and young panicles, and localized in cytoplasm and nucleus. Ectopic overexpression of OsPFA-DSP2 in rice increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Additionally it caused a strong HR that becomes macroscopically apparent on day 1 post-infection (pi) at region I (the site of pathogen infection) (Figure 1A). Changes in Fv/Fm were already detectable after 3 hpi at region I. Twenty-four hpi there was also a remarkable decrease in Fv/Fm at the site of the MgCl 2 treatment (data not shown) consistent with previous studies [20,21]. The meaning of Fv/Fm is maximum fluorescence yield of photosystem II (PS II).…”
Section: Resultssupporting
confidence: 88%
“…Additionally it caused a strong HR that becomes macroscopically apparent on day 1 post-infection (pi) at region I (the site of pathogen infection) (Figure 1A). Changes in Fv/Fm were already detectable after 3 hpi at region I. Twenty-four hpi there was also a remarkable decrease in Fv/Fm at the site of the MgCl 2 treatment (data not shown) consistent with previous studies [20,21]. The meaning of Fv/Fm is maximum fluorescence yield of photosystem II (PS II).…”
Section: Resultssupporting
confidence: 88%
“…Presently, MAPKs have been characterized in higher plants and the importance of Tyr phosphorylation in plant cells cannot be ignored. MAPKs play a vital role in the signal transduction pathways in higher plants [ 124 ]. It is well known that PTPs plays a major role in regulation of MAPK cascade and their expression is often induced by various stress signals [ 124 ].…”
Section: Functional Role Of Protein Tyr Phosphorylation and Dsp In Plmentioning
confidence: 99%
“…MAPKs play a vital role in the signal transduction pathways in higher plants [ 124 ]. It is well known that PTPs plays a major role in regulation of MAPK cascade and their expression is often induced by various stress signals [ 124 ]. For example, Arabidopsis MPK6 is activated by various pathogenic stimuli and abiotic stress signals [ 126 , 127 ].…”
Section: Functional Role Of Protein Tyr Phosphorylation and Dsp In Plmentioning
confidence: 99%
“…Several of these genes belong to gene families involved in resistance in other plant pathogen systems, including an oxidoreductase (Montesano et al 2003 ), an aspartokinase (Stuttmann et al 2011 ) and a proteasome subunit (Yao et al 2012 ), which are conserved between rice and B. distachyon . There is also a glutathione S-transferase (Dean et al 2005 ) and a transcription factor BTF3 (Huh et al 2012 ) found only in the rice syntenic region, as well as a protein kinase C (Subramaniam et al 1997 ), protein tyrosine phosphatases (He et al 2012 ), glycosyltransferases (Langlois-Meurinne et al 2005 ) and a NBS-LRR gene (Loutre et al 2009 ) found only in the B. distachyon syntenic region. There is no favourite candidate gene in the interval for the moment.…”
Section: Discussionmentioning
confidence: 99%